Implementasi Manajemen Pengawasan Hadapi Problematika Pengelolaan Wakaf - Siti Jubaidah; Chuzaimah Batubara (Jurnal Akuntan Publik, 2023)
This research is based on the desire to analyze the role of supervisory management in dealing with waqf management problems. The analysis tool is a qualitative method used by the author, namely to fill in the data or information collected with the final result in the form of writing. This method is used to describe and explain management strategies for dealing with waqf problems through gathering information and studying documents, such as e-books, journal articles, and papers. The ideas that will be put forward highlight: first, the concept of waqf; second, the legal basis of waqf; third, the waqf supervisory management function; fourth, productive waqf and its management in Indonesia.The research results conclude that basically, the problem of supervision is something that is absolutely necessary. For hundreds of years, waqf in Indonesia has not received serious supervision. As a result, quite a lot of waqf assets were neglected and some of the waqf assets were even lost. The waqf supervision process is part of waqf management. The management function includes 4 things, namely: planning, organizing, actuating and controlling.